Inequalities and the COVID-19 pandemic: Pandemic as a force that (still) affects increasing inequalities - Krstić, Zoran (Sociološki pregled, 2023)
In the paper we analyze the effect of the COVID-19 on the increase or decrease in equalities. In the societies with stagnating income, epidemics have had a tendency of decreasing inequalities, and that is why they are defined as malign forces leading to the fall in inequalities. On the other hand, in the societies with increasing income, their authority was omitted under the supposition that they can no longer be an active factor of the increase or decrease in inequalities. In that respect, in our paper we will tr to point to a still significant effect of epidemics (primarily global ones, i.e., pandemics) in the countries with increasing income as well, but also to their currently quite different logic, because they are not only a relevant factor, but they also follow inverse logic as well – they lead to increasing inequalities.
Keywords: COVID-19 pandemic; social inequalities; capitalism